Technical Road Function Wellness Test on the Simpang Kelayang – Lubuk Sitarak Road Section, Indragiri Hulu District - Duwi Putra; Sahriyal; Sri Guntur S (International Journal of Advance Social Sciences and Education (IJASSE), 2024)
The Simpang Kelayang – Lubuk Sitarak road section plays a crucial role in facilitating the distribution of goods and services within the regency. Assessing the road's functional adequacy from a technical standpoint is essential to identify its fitness and determine the reasons for any functional deficiencies. The analysis of road functional tests involves measuring deviations from field conditions against technical standards, including geometric road technicalities, pavement structure, complementary building structures, spatial utilization, traffic management, and road equipment. The method utilized divides road segments according to the Minister of Public Works Regulation No. 11/PRT/M/2010. Results indicate that the Simpang Kelayang – Lubuk Sitarak road section (STA 0+000 – STA 2+010) falls into the category of conditional functional fitness (LS), indicating suitability for operation but requiring recommended technical improvements. Generally, the lack of road functional adequacy in this section stems from failure to meet technical standards in road technical aspects.